A worldwide event-based debris flow barrier dam dataset from 1800 to 2023 - H. Cheng; H. Cheng; K. Hu; K. Hu; S. Liu; S. Liu; X. Zhang; X. Zhang; H. Li; H. Li; Q. Zhang; Q. Zhang; et al. (Earth System Science Data)
Debris flows, as a special kind of landslide, often block rivers to form barrier dams and trigger a series of disasters such as upstream aggradation and outburst floods. The understanding of debris flow barrier dams (DFBDs) is poor, mostly due to existing studies focusing on individual events and a lack of summarization of multiple DFBD events. The existing global or regional datasets of landslide barrier dams (LDs) contain only a few cases of DFBDs and ignore the differences between DFBDs and other landslide barrier dams (LDs), such as the dams of rock slides, debris avalanches, or earth slides. To fill this gap, we reviewed 2519 high-quality literature and media reports. Focusing on identified debris flow damming events, a rigorous data review and validation process was conducted using Google Earth. A systematic approach was employed to prioritize conflicting information from various data sources. Consequently, a global dataset was compiled, encompassing 555 historical DFBDs from 1800 to 2023.